THE IMPORTANCE OF "ELECTION" PROCESSES IN THE DEVELOPMENT OF DEMOCRATIC REFORMS, THE ESSENCE OF THE MIXED ELECTORAL SYSTEM (World Bulletin of Management and Law, 2024)
The article discusses the role and importance of the electoral system in a democratic society, its promising reforms, and the fact that democratic elections are the complete opposite of resolving issues in the sphere of government by force. Through this article, we can learn about the concept of election, the main directions of formation of state power through election and appointment